The inequality in Chile economic, political and social impacts - Seifertová, Zuzana; Gutiérrez Chvalkovská, Jana; Hidalgo Redondo, Oscar; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2014)
Chile is one the most developed countries in Latin America with stable market-oriented economy and sustainable economic growth, becoming the first South American country to join the OECD. Nevertheless, it is also the country with the highest inequality of income in the OECD and one of the most unequal countries in the world. The biggest challenge for the next decade seems to be the reduction of inequalities and poverty. To achieve these goals, Chile needs to implement better policy in the area of production, innovations, finances, but also health and education. The thesis examines the development of inequality in Chile, its current situation and the impacts of inequality on the society, focusing on the problematic areas such as education and health. Additionally, it presents possible solutions and recommendations for Chile to reduce the high level of inequalities, including the external help. The main resources used for the analysis are the information published by the World Bank, OECD or European Commission and complemented with statistics and reports of Chilean government.
Vedoucí práce: Jana Gutiérrez Chvalkovská
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2014
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2014
Způsob přístupu: Internet
Keywords: ekonomická a regionální studia latinské ameriky [obor dipl. práce]; diplomové práce; master's theses